Asymmetry in genitalia does not increase the rate of their evolution - Eberle, J.; Walbaum, Wiebke; Warnock, R. C. M.; Fabrizi, S.; Ahrens, D. (Molecular Phylogenetics and Evolution, 2015)
Left-right asymmetry is a frequently encountered phenomenon in the copulation organs of insects. While various causes have been proposed for genital asymmetry, we raise the question of whether asymmetry might facilitate, or even accelerate, morphological divergence of genitalia between species. We tested this hypothesis in the scarab chafer genus Schizonycha, which comprises species with symmetric as well as asymmetric male genitalia. Morphometric analyses were conducted in the context of their phylogeny, inferred from mitochondrial and nuclear ribosomal DNA sequence data (cox1, rrnL, and 28S) for a sample of 99 South African specimens. , including 34 species and 5 outgroup taxa. Trees were reconstructed with maximum likelihood and Bayesian analysis. The extent of asymmetry and the variation of male copulation organs were analyzed with Generalized Procrustes analysis (GPA), by quantifying shape divergence of the parameres. We found a continuous transition in the degree of asymmetry among the investigated species. Ancestral state reconstruction revealed multiple origins and a high degree of evolutionary plasticity of paramere asymmetry in Schizonycha. However, no significant correlation between evolutionary rates of paramere shape divergence and the degree of paramere asymmetry was found, and so we conclude that asymmetric genitalia in Schizonycha do not increase the rate of genital shape divergence.
CRIS-Team Scopus Importer:2020-10-13
Keywords: Coleoptera; Directional asymmetry; Male genitalia; Morphological rates; Scarabaeidae; Schizonycha